(untitled) (Paliativní medicína, 2021)
The specialty of Nephrology has a proud history of clinical care, technical innovation and research. In the modern era, however, the specialty has recognised several major challenges. They include the growing number of older, co-morbid patients with end stage kidney disease (ESKD), the clinical uncertainty of whether or not to commence dialysis on patients in this cohort, the challenges of symptom management, the reduced quality of life of patients on dialysis and the appropriate care of the dying patient. Gradually, a sub-discipline of Nephrology and Palliative Care emerged in response to those challenges – Renal Supportive Care (RSC). This paper will examine the main aspects of Renal Supportive Care including the foundation principles, the basics of practice and the steps in creating a RSC service.